Albania : Staff Report for the 2016 Article IV Consultation, Seventh Review Under the Extended Arrangement, and Request for Waiver of Applicability and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Albania. (IMF Staff Country Reports; Country Report ;, 2016)
This paper presents an overview of recent economic developments, outlook, and risks of the Albanian economy. Over the past few years, Albania has successfully maintained macroeconomic stability amid a turbulent external environment. A sizable fiscal consolidation is underway, and public debt is projected to start decreasing in 2016. However, growth remains sluggish due to a weak euro area recovery and risk-averse banks. The policy mix focuses on fiscal adjustment, while supporting growth through gradual monetary easing. The key policy priorities are to lower fiscal vulnerabilities through continued consolidation, revive private sector credit by cleaning up bank balance sheets, and continue implementing growth-friendly structural reforms.